Analysis of the Relationship between Interest and Learning Independence with High School Students' Biology Learning Outcomes - Rahmah, Syifana; Ria Yulia Gloria; Nurjannah, Laita (Ilmu Inovasi Nusantara, 2024)
This research aims to determine the relationship between interest in learning and learning independence with students' biology learning outcomes. This research uses a quantitative approach to analyze data. The research population was students of the MIPA MAN 2 Kuningan class for the 2021/2022 academic year with a sample of 98 students using a purposive sampling technique. Instruments for collecting data use questionnaires and documentation. This research data was analyzed using descriptive and inferential statistical techniques. The research results concluded that 1) the relationship between interest in learning and biology learning outcomes has a significant and positive relationship, with a correlation contribution in the weak category, namely 5.4%. 2) the relationship between learning independence and biology learning outcomes has a significant and positive relationship, with a correlation contribution in the weak category, namely 11.4%.